Multidimensional Healthy Adult Scale: Development and validation of a measurement tool to understand how the Healthy Adult works in a Turkish population - Duygu Yakın; Eva Billen; Raoul Grasman; Arnoud Arntz (PLoS ONE, 2026)
Healthy Adult (HA), a key schema therapy construct, represents the individual’s ‘healthy’ state, characterized by balancing personal and others’ needs within a realistic perspective. We developed the Multidimensional Healthy Adult Scale to explore how various dimensions of the HA contribute to different aspects of well-being and tested its factor structure and psychometric properties. Data were collected from 472 participants (24.1% male, 75.5% female) between the ages of 18 and 60. The items of the scale were generated based on a qualitative study conducted in Türkiye. Data were analyzed using Confirmatory Factor Analysis and Structural Equation Modeling in Lavaan, which demonstrated a strong fit for the measurement and predictive models. The Bond, Balance, and Battle factors, along with the overarching HA, showed good fit. Low Balance scores were associated with higher psychopathology and negative affect, while high Battle scores were associated with greater life satisfaction and positive affect. Although Bond correlated positively with Balance and Battle, high Bond scores, when controlling for the others, were linked to increased psychopathology and negative affect. These results provide evidence for a multidimensional structure of the HA. Further validation of the scale and clarification of Bond’s role is needed for clinical insights.